2015
DOI: 10.1016/j.algal.2015.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater treatment and microbial communities in an integrated photo-bioelectrochemical system affected by different wastewater algal inocula

Abstract: Integrated photo-bioelectrochemical (IPB) systems are a newly emerging technology for sustainable wastewater treatment through synergistic cooperation between microbial fuel cells (MFCs) and algal bioreactors. This study aimed to advance our understanding of the IPB performance in contaminant removal and bioenergy production and how IPB function is affected by different algal-bacterial inocula. Fed with a synthetic solution, the IPB system could achieve more than 90% removal of solution organic compounds and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 49 publications
(59 reference statements)
0
17
0
Order By: Relevance
“…This genus was only identified using the MP Bio extraction kit, suggesting the possible role of extraction techniques in bacterial community composition analysis. It should be noted that algal reference sequences are not typically as well represented as bacteria in 16S rRNA sequence databases, and that even more careful targeting (e.g., 18S rRNA), could lead to large proportions of unidentified sequences (Xiao et al, 2015).…”
Section: Microbial Communities In the Hrapsmentioning
confidence: 99%
“…This genus was only identified using the MP Bio extraction kit, suggesting the possible role of extraction techniques in bacterial community composition analysis. It should be noted that algal reference sequences are not typically as well represented as bacteria in 16S rRNA sequence databases, and that even more careful targeting (e.g., 18S rRNA), could lead to large proportions of unidentified sequences (Xiao et al, 2015).…”
Section: Microbial Communities In the Hrapsmentioning
confidence: 99%
“…Actually, the cathode contains mixed population of algae and bacteria, and the synergistic performance of algal-bacterial consortium is important for IPB performance [37]. For example, some algal taxa (e.g., Chlamydomonas reinhardtii, Chlorella vulgaris) have strong tolerance ability to treat various wastewater and a fast growth rate [38], while bacterial taxa Rubrimonas cliftonensis was reported to be capable of nitrate reduction [14]. Studying the working mechanism of these species will help not only the improvement of IPB performance but also the promotion of model functions to give better predication on selecting suitable microbial species.…”
Section: Perspectivementioning
confidence: 99%
“…It was found that 92.4% soluble COD (chemical oxygen demand), 63% total nitrogen (TN) and 82.3% total phosphorus (TP) could be removed, and the energy production (including electricity and biomass biofuel) could theoretically compensate for energy consumption of the IPB system [9]. The algal-bacterial community in the cathode can help nutrient removal in IPB, and certain photoautotrophs (e.g., Leptolyngbya) or chlorophytes (e.g., Acutodesmus) were found as significant species in the community [14].…”
Section: Introductionmentioning
confidence: 99%
“…Sensitivity analysis can also assist in parameter tuning for accelerated model construction. Other innovated applications in BES also need new parameters to analyze the system performance, such as growth rate of algal biomass for integrated photo-bioelectrochemical system (IPB), and the constant for hydrogen production rate in microbial electrolysis and desalination cells (MEDC) [120][121][122].…”
Section: Sensitivity Analysis Of Model Parametersmentioning
confidence: 99%